GREEN HOUSE CONTROL SYSTEM (International Journal of Food and Nutritional Sciences, 2022)
Greenhouse control systems are advanced technological solutions designed to optimize thegrowing conditions within greenhouses, enhancing crop yield, quality, and resource efficiency.By utilizing sensors, actuators, and automation technologies, these systems monitor and regulateenvironmental parameters such as temperature, humidity, light, and CO₂ levels. This reviewexplores the evolution, current trends, and future potential of greenhouse control systems,highlighting their critical role in sustainable agriculture. The paper discusses various controlstrategies, from manual to fully automated and AI-driven systems, and examines their strengths,weaknesses, and applications. It also addresses the challenges and future directions fordeveloping more sophisticated and accessible control systems to meet the growing demand forsustainable food production.